2007
DOI: 10.1002/jbm.b.30718
|View full text |Cite
|
Sign up to set email alerts
|

Internal adaptation and some physical properties of methacrylate‐based denture base resins polymerized by different techniques

Abstract: This study evaluated the internal adaptation, porosity, transverse and impact strength of three denture base polymers: (1) conventional heat-polymerized, (2) microwave-polymerized, and (3) injection-molded resins. Internal adaptation was measured by weighing a vinyl polysiloxane film reproducing the gap between the denture base and the metallic master model of an edentulous maxilla. The measurements were performed immediately after finishing and after 30-day storage in water. Porosity was evaluated by weighing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 63 publications
0
29
0
2
Order By: Relevance
“…Although a standardized process in the weighing the impression material for evaluating denture adaptation has emphasized 11,18) , further variables, such as the mixing ratio, type of material, viscoelastic behavior with time and temperature, and applied load should also be considered 33) . The previous results reported an increase in the weight of the impression material trapped under the denture base after storage in water for 14-30 days 19,34) , while the maximum palatal gap of several denture bases decreased after storage in water for more than 14 days 24) . Therefore, a repeated measurement method for weighing impression materials of the denture base may produce an incorrect measure of the adaptation accuracy.…”
Section: Discussionmentioning
confidence: 84%
“…Although a standardized process in the weighing the impression material for evaluating denture adaptation has emphasized 11,18) , further variables, such as the mixing ratio, type of material, viscoelastic behavior with time and temperature, and applied load should also be considered 33) . The previous results reported an increase in the weight of the impression material trapped under the denture base after storage in water for 14-30 days 19,34) , while the maximum palatal gap of several denture bases decreased after storage in water for more than 14 days 24) . Therefore, a repeated measurement method for weighing impression materials of the denture base may produce an incorrect measure of the adaptation accuracy.…”
Section: Discussionmentioning
confidence: 84%
“…Information on this parameter is important for clinical application of a denture base material and all results satisfied the criteria in ISO 1567 for denture base resins, which specify that the mean breaking force of acrylic resin should not be less than 55 N. 32 Previous studies have shown similar results for the control groups of both acrylic resins. Machado et al 7 observed a mean flexural strength of 116 13 MPa for heat-polymerized PMMA denture base, and Ganzarolli et al 33 observed 97.55 MPa for microwave-polymerized PMMA resin. To our knowledge, no previous published report has studied acrylamide addition to PMMA denture base resins.…”
Section: Discussionmentioning
confidence: 99%
“…Tridimensional distortion of the denture bases was measured by the method of weighing a silicone rubber film reproducing the gap between resin base and metallic master cast 14. A standardized portion of flow type vinyl polysiloxane (3M ESPE Express, St. Paul, USA) was prepared and coated the internal surface of each resin base, which was repositioned over the master cast and kept in place under an axial load of 40 N. The resulting vinyl polysiloxane film was trimmed at the borderline mark of the master cast and weighed using a precision balance (Mettler Toledo, model AG204, Switzerland) (Figure 1).…”
Section: Methodsmentioning
confidence: 99%